Genetic variation of human neutrophil Fcγ receptors and SIRPα in antibody‐dependent cellular cytotoxicity towards cancer cells. Issue 2 (2nd November 2017) - Treffers, Louise W.; Zhao, Xi Wen; van der Heijden, Joris; Nagelkerke, Sietse Q.; van Rees, Dieke J.; Gonzalez, Patricia; Geissler, Judy; Verkuijlen, Paul; van Houdt, Michel; de Boer, Martin; Kuijpers, Taco W.; van den Berg, Timo K.; et al.
Abstract: The efficacy of cancer therapeutic antibodies varies considerably among patients. Anti‐cancer antibodies act through different mechanisms, including antibody‐dependent cellular cytotoxicity (ADCC) triggered via Fcγ receptors (FcγR). This phagocyte ADCC can be promoted by interference with CD47‐SIRPα interactions, but the magnitude of this enhancement also varies among individuals. Both FcγR and SIRPα display considerable genetic variation, and we investigated whether this explains some of the variability in ADCC. Because of linkage disequilibrium between FcγR variants the interpretation of previous reports suggesting a potential link between FcγR polymorphisms and ADCC has been troublesome. We performed an integrated genetic analysis that enables stratification. ADCC by activated human neutrophils towards Trastuzumab‐coated breast cancer cells was predominantly dependent on FcγRIIa. Neutrophils from individuals with the FcγRIIa‐131H polymorphic variant displayed significantly higher killing capacity relative to those with FcγRIIa‐131R. Furthermore, ADCC was consistently enhanced by targeting CD47‐SIRPα interactions, and there were no significant functional differences between the two most prevalent SIRPα polymorphic variants. Thus, neutrophil ADCC capacity is directly related to the FcγRIIa polymorphism, and targeting CD47‐SIRPα interactions enhances ADCC independently of FcγR and SIRPα genotype, thereby further suggesting that CD47‐SIRPα interference might be a generic strategy for potentiating the efficacy of antibody therapy in cancer. Abstract : ADCC of activated human neutrophils towards Trastuzumab‐opsonized breast cancer cells was strictly FcγRIIa dependent with the FcγRIIa‐131H polymorphic variant showing increased cytotoxicity over FcγRIIa‐131R. There was no functional difference between the two principal polymorphisms in the inhibitory immunoreceptor SIRPα, further supporting the idea that CD47‐SIRPα checkpoint blockade can provide a generic approach to potentiate antibody therapy against cancer.